Measurement and Spatial Analysis of Internal Development Zones in Isfahan Metropolitan Area 3 - Shafaghi, Sirous; Mokhtari, Reza; Abadi, Malek; Behmanesh, Behzad (International Journal of Engineering and Technology, 2018)
The lack of macro urban development strategies, the growth of worn out texture, dispersed and heterogeneous growth, marginalization, environmental problems, and physical development have created an inappropriate landscape for the metropolis of Isfahan. Accordingly, the aim of this study is to measure the spatial analysis of internal development zones in Isfahan metropolitan area 3. To determine the appropriate internal development zones of the ANP model and its cluster analysis, the nearest neighbor and the Getis-Ord model have been used. The results of the research show that, the areas with a high, low and very low priority for internal development are 97, 91 and 430 hectares, respectively. Hence, about 188 hectares of texture in the 3rd district of Isfahan is prone to internal development. Based on the average method of the nearest neighbor, the distribution pattern of the high priority areas has a z-scoer of 20.85 and p-value with a score of 0.000, which indicates a fully clustered pattern of distribution of these lands at a level of 99% It should be.The conclusion show that priority intervention areas are in the north and center and low priority clusters in the southern part of the region. Therefore, neighborhoods with values above the mean in the center and somewhat in the north and west of the city and neighborhoods have lower values than the mean in the south and east of Isfahan.Â Â